Upaya Meningkatkan Perekonomian Masyarakat Desa Tegalharjo Melalui Inovasi Pemanfaatan Pepaya Menjadi Abon - Siti Aimah; Eko Budiywono; Moh. Harun Al-Rosid (IAI Darussalam, 2019)
Tegalharjo village is a village in Glenmore sub-district, Banyuwangi district, which has a very large plantation area with a variety of plants. One of the plants that thrives on plantations and people's homes is the papaya tree. But the use of papaya as a village's potential to improve the economy of citizens is less than optimal. Papaya is generally left to rot in the trees, sometimes sold cheaply with a maximum price of Rp1,500.00 a kilo gram and even ironically it is only used as animal feed. Meanwhile the majority of housewives only depend on the family economy for their husbands' work as farmers, farm laborers, very few who are self-employed and plantation labour majority. Seeing this, there needs to be innovations that can increase the economic value of papaya fruit. One of them by processing papaya fruit into shredded. After being processed into shredded, the selling value automatically increases from a kilo of Rp 1,500.00 to Rp 5,000.00 in 150 grams. This innovation was carried out by the service team through mentoring activities and training in making shredded papaya fruit.